Kepemimpinan, Kepuasan Kerja dan Motivasi terhadap Kinerja Pegawai - Roy Sahputra Saragih; Hengki Mangiring Parulian Simarmata (JURNAL ILMIAH MANAJEMEN & BISNIS, 2018)
This study aims to analyze the influence of leadership and satisfaction on employee performance with motivation as an intervening variable. The sample used was 100 respondents. Data collection method using questionnaires and interviews. The data analysis technique used in this study is Path analysis. The results of this study prove that there is a significant influence between employee performance and leadership, leadership with satisfaction, leadership with work motivation, satisfaction with work motivation, employee performance with satisfaction, employee performance with work motivation. Path analysis shows leadership, satisfaction, and work motivation influences changes in employee performance variables.